Development of SPLTV Learning Media using the Clickteam Fusion 2.5 Mobile Application - Hariyanto, Robby; Wanda Nugraha, Aldila (MultiTech Publisher, 2024)
This development research is driven by technological advances that continue to develop rapidly but have not been utilized optimally by educators. This can be seen from the lack of innovation in creating interesting learning. Monotonous learning activities cause students to feel bored and affect their learning outcomes, especially in the material of the three-variable linear equation system. This research aims to develop a learning media based on the Clickteam Fusion 2.5 mobile application that is valid, practical, and effective. This research uses the Research and Development (R&D) development method. The model used in the development process of ADDIE. The subjects of this study are teachers and students of class X of St. Thomas Aquino Catholic High School Tulungagung which totals 95 students. The data collection method uses validity questionnaires from media experts and material experts, questionnaires of teacher and student responses, and student learning outcome tests. The results of the validity test from media experts showed a score of 90% with a very valid category, while material experts obtained a score of 80% with a fairly valid category. The practicality test by teachers showed a score of 80.86% and by students 89.56%, both in the very practical category. The media effectiveness assessment obtained a score of 89% with the category of very effective.